Analisis Hubungan Zakat, Inflasi, Dan Kemiskinan terhadap Kesejahteraan Masyarakat Di Indonesia - Farizal, Nando; Ramadhan, Mhd Syahwali; Hidayati, Ayu (Borneo Islamic Finance and Economics Journal, 2024)
The Human Development Index (HDI) is a picture of human welfare development in a country. Indonesia has 34 provinces and some provinces still have HDI levels below 70% and are included in the moderate HDI category. This condition can be related to the policies taken from a country both from the strategy of maintaining inflation and reducing poverty levels. The purpose of this study is to analyze, interaction, contribution and causality relationship between Inflation and poverty rate and human development index in provinces in Indonesia. The theory used in this study is related to macro variables in the form of inflation and poverty rate and Human Development Index. This research is a quantitative study using secondary data with a sampling technique with saturated sampling of 34 samples, and analyzed using the VAR method with statistical aids Eviews 10 computer program. The results showed based on the Vector Error Corection Model (VECM) analysis that the poverty rate has an influence of 10.4% Based on the Impulse Response Function (IRF) analysis, the poverty rate response and finally the inflation variable where the dynamic shock is stable between year 15 to year 20. The results of the Forcast Error Variance Decomposition (FEVD) analysis show that the poverty rate is the variable that has the greatest contribution to other variables, which is 31.44% and 4.76%. The variable with the lowest response and contribution to other variables is the inflation variable at 3.79%.